Prototype of Riding Accident Detection System Using R3 SMD Microcontroller Based on GPS and IoT - Setiadi, Teguh; Wijayanti, Aris (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
The incidence of road accidents is quite high. This is due to driver negligence. Based on these problems, a driving accident detection system was created. The system uses vibration sensors, tilt sensors, and pressure sensors as inputs to detect driving accidents. The system is supported by an Arduino uno kit with an R3 SMD microcontroller as the brain to process data from vibration, tilt, and pressure sensors, and is equipped with GPS and ESP32. Then, the output to ESP32 will send notification information to Telegram by detecting GPS, so that it will automatically send notification of driving accident coordinates. From the making of this system, it can be concluded that, if a driving accident occurs, it will automatically send information directly to the victim's family quickly. The system will work if the sensor is detected and will send data to the phone number stored in the database. So that victims can be handled more quickly to avoid casualties.